ORGAN HARVESTING TERHADAP PRAKTISI FALUN GONG OLEH CHINESE COMMUNIST PARTY DI TIONGKOK BERDASARKAN UNITED NATION CONVENTION AGAINST TORTURE AND OTHER CRUEL, INHUMAN OR DEGRADING TREATMENT OR PUNISHMENT (UNCAT) - Mela Kristina; Maria Maya Lestari; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Human rights are widely considered to be the fundamental moral rights of people, in which necessary for human dignity. Human rights thus serve a greater social purpose, and it is a legal system that informs us at a certain point in time when rights are considered to be the most basic in society. Even if human rights are considered inalienable, the moral attributes of the people that the state cannot violate this, rights still have to be identified, that is, they are constructed by humans and codified in the legal system.The type of research carried out through normative-juridical research where this research is conducted on the basis of legal principles which started from certain written authorities as well as priorly identifying the provisions that has been enshrined in certain law. In this study, the data sources used were secondary data with primary, secondary and tertiary legal materials carried out.The results obtained through the research proves that, there are three main points that can be concluded. First, in the eyes of international law, both ordinary prisoners and political prisoners/prisoners of conscience must be treated like self-determined humans. This is clearly stated in the Bill of Rights, even prisoners are prohibited from being treated inhumanely. Second, torture of humans is a serious violation of human rights. Organ harvesting without consent has been considered a crime under international law, including organ trafficking is illegal in most countries. In this Falun Gong case, the members' organs were removed without the consent of the prisoners or the prisoners' families. Third, every action taken, eventually there comes responsibility. Furthermore, this is applicable in the international community. If a country commits an internationally wrongful act, in another sense, an act committed by a country in which the act is deemed to violate international legal obligations, both arising from treaties and international customary law that is erga omnes in nature, there will arise state responsibility/liability.Keywords: Human Rights – Organ Harvesting – State Responsibility